Calodium hepaticum (Nematoda: Capillariidae) in wild rodent populations from Argentina - Fantozzi, María Cecilia (2018)
Calodium hepaticum (Nematoda; Capillariidae) is a parasitic nematode of mammals with a cosmopolitan distribution. Adults of this nematode can infect the liver of many mammalian species, including humans, but the main hosts are members of the superfamily Muroidea. Among these, Rattus spp. have the highest apparent prevalences reported worldwide. There are only two reports of C. hepaticum infecting Sigmodontinae species (Muroidea: Cricetidae). In this survey, we examined the occurrence of C. hepaticum in two assemblages of Sigmodontinae rodents from Argentina (Santa Fe and Entre Ríos provinces). The diagnosis was made by morphological features, histopathological exam, and molecular characterization of 18S ribosomal RNA gene region. Here, we show that C. hepaticum is a common parasite of Sigmodontinae. We report the infection in six species (all new hosts): Akodon azarae, Calomys callidus, Calomys venustus, Oligoryzomys flavescens, Oligoryzomys nigripes, and Oxymycterus rufus. This is the first report of C. hepaticum in Sigmodontinae rodents from Argentina and the second record in this subfamily for South America. It is also the first confirmation of C. hepaticum infection in Sigmodontinae by molecular diagnosis. The genetic findings and the prevalences observed, together with the existing information on C. hepaticum, lead us to propose that Rattus spp. brought C. hepaticum to the New World exposing Sigmodontinae rodents, which are frequently infected by this parasite. The high prevalence of infection in A. azarae (41.2%) suggests that this host may be playing an important role in C. hepaticum dynamics in the New World.